Omphalocele in three generations with autosomal dominant transmission. Issue 3 (1st March 2002) - Kanagawa, S L; Begleiter, M L; Ostlie, D J; Holcomb, G; Drake, W; Butler, M G
Abstract : We report a family with nine subjects over three generations affected with an omphalocele requiring surgical intervention within the first few days of life. Because of the vertical transmission and male to male inheritance in our family, we conclude that an autosomal dominant gene caused the omphalocele in the affected family members. The paternal great grandfather of the proband was not clinically affected but produced two children with omphaloceles with different spouses.